1976
DOI: 10.1111/j.1365-2923.1976.tb00434.x
|View full text |Cite
|
Sign up to set email alerts
|

The attainment of specified objectives by medical students in different learning environments

Abstract: Summary Medical students were provided with behavioural objectives for the problem solving phase of their curriculum. They were assigned for 11 weeks to various hospital settings that differed in the presence or absence of structured classes, the expertise of the teaching staff, the amount of instruction time and the types of learning experiences. At the end of that time, the students took the same examination to measure attainment of the objectives. The only variable that was associated with significantly dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The teachers' attitudes to the taught topics have not changed, as far as they were aware. Berner & Tremonti (1976) showed that students learned better when scheduled objectives were accompanied by classes; the mixture has not varied in our curriculum over the period of study. Hence the only inhomogeneities expected among our students were related to their possession of a first degree, and possibly a gender difference among various parts of the subject.…”
Section: Discussionmentioning
confidence: 89%
“…The teachers' attitudes to the taught topics have not changed, as far as they were aware. Berner & Tremonti (1976) showed that students learned better when scheduled objectives were accompanied by classes; the mixture has not varied in our curriculum over the period of study. Hence the only inhomogeneities expected among our students were related to their possession of a first degree, and possibly a gender difference among various parts of the subject.…”
Section: Discussionmentioning
confidence: 89%